Thailand's political history from the 13th century to recent times - Terwiel, B. J. (River Books, 2011)
Moving into the twentieth century it traces the emergence of the Thai nation state, the large-scale investments in modern infrastructure and the concomitant economic expansion that have occurred since the 1950s onwards.